Dampak Hedonic Shopping Values, Sales Promotion, dan Shopping Lifestyle Terhadap Impulse Buying Pada Generasi Digital Native di TikTok Shop - Dini Faradina; Edwin Zusrony; Tantik Sumarlin (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the relationship between enjoyment of shopping, the impacts of sales promotions, shopping as a way of life, and the tendency to buy on impulse of the respondents living in the digital age. In this case, we used the quantitative method. The primary data was obtained from the respondents through a closed-ended questionnaire which used a 5-point Likert scale. In this case, the respondents selected for the study were all users of the Tik Tok Shop app who were between the ages of 19 and 38 and were residing in Kendal Regency. In this case, the purposive method was used which as a result the total number of respondents reached 60. The data was subjected to multiple linear regression and was run on SmartPLS application version 4.1.1.2. The research results concluded that the hedonic shopping values did not significantly affect the impulse buying tendency whereas the sales promotions and shopping as a way of life had significant positive effects on impulse buying in this case. At the same time, hedonic shopping values, sales promotions and shopping as a way of life had significant positive effects on impulse buying. The TikTok Shop marketers can use these findings in pinpointing the major factors behind the impulse buying tendency.